A linguagem em uso na sala de aula: oportunidades para ler e escrever no contexto do projeto didático autoral docente - Flávia Helena Pontes Carneiro (2019)
This research paper analyses the opportunities to read and write discursively created in a classroom in the 3rd year of elementary school in a public school of Belo Horizonte municipal network and inscribes itself in the field of literacy studies as a social practice. The theoretical-methodological framework adopted is the Interactional Ethnography (GREEN; DIXON, 1993; CASTANHEIRA; CRAWFORD; DIXON; GREEN 2001 e CASTANHEIRA 2000, 2004) anchored in the studies of Symbolic and Cognitive Anthropology (GEERTZ, 1983; SPRADLEY, 1979, 1980) and the combination of discourse analysis studies, such as Interactional Sociolinguistics (GUMPERZ, 1982, 1986) and Critical Discourse Analysis (FAIRCLOUGH, 1993; IVANIC, 1994). The participant observation (SPRADLEY, 1980) in the field working during a year relied on the use of ethnographic tools such as audio and video records and field notebooks. The concepts of intertextuality (BLOOME; EGAN-ROBERSTON, 1993) and intercontextuality (FLORIANI, 1994) were used to examine how the text was constructed interactively in the classroom and to analyze the opportunities for reading and writing textualized in the discourse of participants. The teacher's author didactic-project observed in action characterized from the studies of (MATENCIO, 2001), (BUNZEN, 2009), and (ROCKWELL 2012), allowed to identify, among other aspects, how the teacher selected the objects of teaching and how she axiologically positioned in the discourse, producing a mark in creating opportunities for reading and writing. The teacher's author didactic-project observed in action characterized from the studies of (MATENCIO, 2001), (BUNZEN, 2009), and (ROCKWELL 2012), allowed to identify, among other aspects, how the teacher selected the objects of teaching and how she axiologically positioned in the discourse, producing a mark in creating opportunities for reading and writing. The study pointed to the literacy practices developed in the school sphere created and marked by the teacher‟s value appreciation. The reading of memes was conditioned by the passage from the non-school sphere to the school sphere changing the ways of reading and producing meanings. The teacher created contexts for the digital literacy practices, in the work as the cultural theme "research", in which reading and writing were used to solve challenges, enabling the construction of conceptual, attitudinal and procedural knowledge needed to read and write in digital environments. In the culture of this classroom, the process of learning how to research was considered more important than the presentation of a product. The discursive aspects analyzed in the literacy practices carried out in the teacher's didactic project point to the need to consider school literacy, as proposed by KLEIMAN (1995, 2007, 2008) and BUNZEN (2009), as sociocultural practices that take place in the school sphere. The study also pointed to the potential of exploring classroom discourse in teacher training courses in the context of literacy as a social practice.